Sexual difference : masculinity and psychoanalysis - Frosh, Stephen (London ; New York : Routledge, 1994)
This critical exploration of issues of gender in psychoanalysis acknowledges and updates the complexity of theory and writing in this area, particularly the way sexual differences can only be thought about from a gendered position.
Book Cover; Title; Contents; Acknowledgements; Finding sexual difference; Psychoanalysis and sexual difference; Inside the dream; Masculine mastery and fantasy, or the meaning of the phallus; The seeds of masculine sexuality; Transgressing sexual difference; References; Name index; Subject index.
Includes bibliographical references (pages 145-148) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Masculinity; Sex differences (Psychology); Psychoanalysis; Sex differences; Identification (Psychology); Psychoanalytic interpretation; Sex Characteristics; Psychoanalysis; Psychoanalytic Theory; Men -- psychology; Identification, Psychological; Psychoanalytic Interpretation; Masculinité.; Différences entre sexes (Psychologie); Psychanalyse; Différences entre sexes; Identification (Psychologie); Interprétation psychanalytique; psychoanalysis; PSYCHOLOGY -- Human Sexuality; Sex differences; Psychoanalytic interpretation; Identification (Psychology); Masculinity; Psychoanalysis; Sex differences (Psychology); Sexo e sexualidade (sociologia); Psicologia; Psicanalise; Men -- Psychology